ANALISIS KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN WISTAWAN DI QUICKSILVER CRUISE - Happy Marini S., Ni Putu; Sudana, I Putu; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 2 (2015): Jurnal IPTA (December 2015)DO - 10.24843/IPTA.2015.v03.i02.p01, 2015)
This research aims to determine the level of interest and satisfaction toward the service of Quicksilver Cruise. The type of data used are qualitative and quantitative data,while for data source is the primary and secondary data. Techniques of data collection is conducted through observation,interviews and  questionnaire. The sampling technique used purposive sampling and applied particular consideration determined by the researcher itself. The method of analysis used likert scale and Cartesian diagram. The research result shows that tourist are satisfied by the service in Quicksilver Cruise, with an average rate of suitability is 72.2 percent. Being used cartesien diagram to analyze the indicators to be a top priority and must be done in accordance with expectations of tourist, such as: safety and comfortable during follow the activities, competent for handling problem, always quick understanding about what’s the guests needed. Indicators are considered important and needed to be maintained its conditions and cruise facilities, friendly service and offering help, cleanliness and neatness of the cruise, safety assurance. Indicators considered less important by tourist but its implementation is quite well done, namely responsiveness in providing clear and concise information. Indicator that overestimated by tourist but it have done verry well, such as the given individual notice toward to the guests.
Keywords: Tourist Satisfation, Service Quality